Impacts of Land use Changes on Urban Heat Islands in Hanoi, Vietnam: Scenario Analysis. (2017) - Trihamdani, Andhang Rakhmat; Kubota, Tetsu; Lee, Han Soo; Sumida, Kento; Phuong, Tran Thi Thu
Abstract: This study aims to investigate the impacts of land use changes brought by the Hanoi Master Plan 2030 (HMP) to the urban heat island (UHI), using the Weather Research and Forecasting (WRF). A scenario analysis was carried out to assess the effectiveness of urban greening for mitigating UHI. The urban climate under the influence of global warming was also investigated by downscaling the results of global climate simulation (MIROC5 RCP4.5) in the scenario analysis for 2030s. The results show that the land use change does not significantly increase the peak average air temperature (Tavg) in urban areas: the peak Tavg remains at almost in the same level of 37 °C. Instead, it increases the number of hotspots and raises the nocturnal Tavg particularly in new urban areas by up to 1 °C. Further, if the green coverage ratio in new urban areas is increased to 30% and the mixed forest is adopted as vegetation type in the green spaces, Tavg is lower by up to 0.5 °C and the hotspots are reduced by up to 28%. Meanwhile, it was found that the urban air temperature is predicted to increase by up to 1.8 °C due to the global warming in 2030s. This increment has surpassed the cooling effect of UHI mitigation through urban greening.